Atomic layer deposition of Cu(i) oxide films using Cu(ii) bis(dimethylamino-2-propoxide) and water. Issue 18 (13th April 2017) - Avila, J. R.; Peters, A. W.; Li, Zhanyong; Ortuño, M. A.; Martinson, A. B. F.; Cramer, C. J.; Hupp, J. T.; Farha, O. K.
Abstract : To grow films of Cu2 O, bis-(dimethylamino-2-propoxide)Cu(ii ), or Cu(dmap), is used as an atomic layer deposition precursor using only water vapor as a co-reactant. Abstract : To grow films of Cu2 O, bis-(dimethylamino-2-propoxide)Cu(ii ), or Cu(dmap), is used as an atomic layer deposition precursor using only water vapor as a co-reactant. Between 110 and 175 °C, a growth rate of 0.12 ± 0.02 Å per cycle was measured using an in situ quartz crystal microbalance (QCM). X-ray photoelectron spectroscopy (XPS) confirms the growth of metal–oxide films featuring Cu(i ).